Single Molecule Real-Time Sequencing and Traditional Cultivation Techniques Reveal Complex Community Structures and Regional Variations of Psychrotrophic Bacteria in Raw Milk - Du, Bingyao; Meng, Lu; Liu, Huimin; Zheng, Nan; Zhang, Yangdong; Zhao, Shengguo; Wang, Jiaqi (Frontiers in Microbiology, 2022)
In this study, we investigated the species composition and diversity of psychrotrophic bacteria in raw milk from Heilongjiang, Inner Mongolia, Gansu, Henan, Anhui, Jiangsu, Chongqing, and Hunan provinces in China using traditional cultivation and PacBio Single Molecule Real-Time sequencing methods. The isolated psychrotrophic bacteria were highly diverse, which composed of 21 genera and 59 species. Pseudomonas accounted for 58.9% of the total genera while Stenotrophomonas and Enterococcus were also highly represented (above 5.0%). In particular, P. azotoformans occurred at a level of 16.9% and P. paralactis, P. lactis, E. faecalis, and P. marginalis were present in relatively high proportions (above 4.0%). Regional differences were found significantly among the test regions except samples from Heilongjiang and Inner Mongolia were similar. Additionally, differences were observed between days in Henan, Anhui, and Jiangsu samples. Therefore, control strategies must be implemented on regional and season basis.